Nghiên cứu gia cố đất bằng các phụ gia vô cơ để xây dựng công trình - Lê, Huy Cứ (2011)
Tác giả: Lê Huy Cứ, ThS; Dương Đăng Khoa, ThS; Nguyễn Minh Tuyển, GS; Nguyễn Thanh Sơn, KS; Lê Huy Cường, KS -- Từ khóa: Gia cố đất; Phụ gia vô cơ